Microsoft Excel 2013 : data analysis and business modeling - Winston, Wayne L. (US : Microsoft, 2014)
Master business modeling and analysis techniques with Microsoft Excel 2013, and transform data into bottom-line results. Written by award-winning educator Wayne Winston, this hands-on, scenario-focused guide shows you how to use the latest Excel tools to integrate data from multiple tables - and how to effectively build a relational data source inside an Excel workbook.
Includes index.
Keywords: Microsoft Excel (Computer file).; Industrial management -- Statistical methods -- Computer programs; Decision making -- Computer programs